Pariwisata Halal: Studi Implementasi di Pantai Tanjung Bias Lombok Barat - Nugroho, M. Setyo; Harianto, Dedi (Institut Agama Hindu Negeri Gde Puda Mataram, 2022)
This study aimed to find out halal tourism implementation model at Tanjung Bias beach west Lombok, also to identify the obstacle that is faced with in that implementation process. This study used qualitative method with field research approach, namely mapping potential and existing condition of Tanjung Bias beach. Subsequently, This study looked for the connection between phenomenon and halal tourism concept. Data collection method used is divided into three: First, Observation in form of direct observation related to Tanjung bias beach existing condition as halal tourism destination. Second, interview to the manager, public sector, local community. Third, documentation study sourced from article, book and relevant references with research topic. Data analysis technique used inductive approach to assist significance various data that is obtained. This research result showed that there are five indicators of halal tourism that have been implemented at Lombok Tanjung Bias beach, such as (1) Service which adopted Islam principle. (2) Service provider has discipline and comprehension Islam theory. (3) Tourism activity was not contradicting with Islam principle. (4) Availability of halal culinary. (5) Availability of hospitable facility for Muslim tourist. Nevertheless, There are three obstacles in halal tourism implementation that was successfully identified, such as: (1) some of merchant booths has not been yet halal certified. (2) privacy service is not available. (3) tourism human resource did not have professional certification.